Diversity of Rotavirus Strain Circulated in Gwangju, Republic of Korea - Kim, Min Ji; Jeong, Hye Sook; Kim, Seon Gyeong; Lee, Se Mi; Kim, Sun Hee; Kee, Hye-Young; Jo, Eun-hye; Park, Hye-jung; Ha, Dong-Ryong; Kim, Eun Sun; Seo, Kye-Won; Chung, Jae Keun (Osong public health and research perspectives, 2014)
The introduction of new rotavirus vaccines into the public sphere makes it necessary to maintain constant surveillance and to heighten public awareness of the appearance of new rotavirus strains. We describe the molecular epidemiology of circulating rotavirus strains after vaccine introduction. We collected a total of 1070 stool samples from children with gastroenteritis from January 2013 to June 2013. The antigenic prevalence of rotavirus group A was distinguished using enzyme immunoassay. The G and P genotypes of enzyme immunoassay-positive samples were determined with reverse transcription-polymerase chain reaction and nucleotide sequencing analysis. Of the 1070 samples collected, 277 (25.9%) tested positive for rotaviruses by enzyme-linked immunoabsorbent assay. The most prevalent circulating genotype G was G1 (51.3%), followed by G2 (34.7%) and G9 (10.8%). The predominant type of genotype P was P[8] (66.1%), followed by P[4] (31.4%). In this study, nine genotypes were found. G1P[8] was the most prevalent (51.8%), followed by G2P[4] (30.5%), G9P[8] (9.9%), and G2P[8] (4.0%). Several unusual combinations (G1P[4], G3P[9], G3P[8], G4P[6], and G9P[4]) were also identified. Molecular epidemiological knowledge of rotaviruses is critical for the development of effective preventive measures, including vaccines. These data will help us monitor the effectiveness of current rotavirus vaccines.